2020
DOI: 10.1016/j.anpedi.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Manifestaciones cutáneas en contexto del brote actual de enfermedad por coronavirus 2019

Abstract: comunes de la infancia. Dada la situación actual y las medidas de prevención del contagio en los pacientes con COVID-19, sean confirmados o de sospecha, es de especial importancia conocer esta sintomatología como parte del cuadro clínico de la enfermedad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 4 publications
1
5
0
4
Order By: Relevance
“…Most of the patients with skin manifestations were middle-aged females, while, patients with chilblain-like lesions were younger (mean age: 40.7 years) and patients with vascular lesions were older individuals (mean age: 72.3 years). These findings are along with other studies about the chilblain-like lesions ( 6 , 19 , 24 , 40 ). Maculopapular lesions were the most common dermatologic presentation of COVID-19 patients that commonly appeared at extremities.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the patients with skin manifestations were middle-aged females, while, patients with chilblain-like lesions were younger (mean age: 40.7 years) and patients with vascular lesions were older individuals (mean age: 72.3 years). These findings are along with other studies about the chilblain-like lesions ( 6 , 19 , 24 , 40 ). Maculopapular lesions were the most common dermatologic presentation of COVID-19 patients that commonly appeared at extremities.…”
Section: Discussionsupporting
confidence: 88%
“…In Spain, with full confinement measures imposed by the national government and coinciding with the pandemic, pediatricians and dermatologists have received, through teledermatology/teleconsultation and social networks, a barrage of diverse images, which have subsequently allowed us to approach some of them by direct physical examination of early and late skin manifestations associated with SARS‐Cov‐2 infection 1‐4 . In particular, acro‐ischemic lesions, similar to chilblain (chilblain‐like), have been highlighted in children and adolescents with little or no symptoms, located at fingers and toes.…”
Section: N = 27mentioning
confidence: 99%
“…With regards to the form of contamination of children and adolescents, studies have shown the predominance of family transmission (n=15), followed by community transmission (n=12). When mentioning presence of a pre-existing disease or condition, most did not specify whether participants had any previous morbidity (n=15); in 10 studies, children and adolescents did not have pre-existing illnesses or poor health conditions (12,(16)(17)(19)(20)(21)(22)24,32,36) ; in the other studies, heart failure (11) , prematurity (13) , previous infection by Streptococcus (23) , hydronephrosis and leukemia (18) and liver diseases or changes (33,40) were highlighted. As for the need for hospitalization, most studies (n=24) reported that children and/or adolescents were hospitalized for a period of 1 to 20 days (Chart 3).…”
Section: Resultsmentioning
confidence: 99%
“…Xing et al, (30) 1 -6y Family transmission NS Yes/NS Yin et al, (31) 9y NS NS Yes/NS Chen et al, (32) 7m -17y Travel history and community transmission NS Yes/NS Morey-Olivé et al, (33) 2m e 6y Community transmission Cholestatic liver disease Yes/NS Liu et al, (34) 11m -9y Community transmission NS NS Chacón-Aguilar et al, (35) 26d NS NS Yes/06 Ji et al, (36) 9 e 15y Travel history No Yes/02…”
Section: Age Group Probable Contamination Of the Disease Pre-existing Disease/condition Hospitalization/ Length (Days)mentioning
confidence: 99%